The Decision Making Process For Business Growth Plan of Kebab Mini Babe Juki - Putri, Citra Andika; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2015)
Abstract - In this globalization era, business competition is getting intense in domestic or global. This phenomenon makes the business leader being more creative and competitive in making the approach to its customer. The strategy they used is about how to grab wider market and serve them well. This phenomenon happens regarding to the variability of consumer needs in every sector, especially in food consumption. Nowadays consumer has several needs and behavior in food consumption depending on several variables such as age, daily activities, and healthy lifestyle. The changing of people’s food consumption pattern opening wide opportunity for side dish business due to the high demand for side dish. Good nutrition, affordable, easy to serve and easy to consume are the most preferred side dish. These are the benefit that Kebab Mini Babe Juki offers to their consumer to consume them as the preferable side dish. The trends and demand for side dish that occur in Indonesian people food consumption’s habit gives Kebab Mini Babe Juki wide opportunity to grow its business. Kebab Mini Babe Juki which already existed for two years is in the situation where the kiosk permanently closed for several reasons. KMBJ take this situation as the turning point to design new strategy for the next business growth plan. Slow growth of the business is one of important factor that encouraging KMBJ to find new strategy in order to gain optimal profit and better growth in the future. In this research, all available options that KMBJ have in finding the right strategy will be analyzed using decision making tools and technique. By using the decision making process, it is hoped that the optimal result could be applied in the real business activities of KMBJ. The business issues exploration explore The Kebab Mini Babe Juki’s business situation in general and its internal issues. Its general business situation will be explained by using PESTEL, Porter’s five forces and business model. Then the internal issues will explore the problem analysis that delivered by fishbone diagram.The business solution started by the data gathering about competitors, supplier, frozen food industry and consumer that delivered by interview and questionnaire then continue with the decision making process that will be done by using SMART Analysis. By analyzing the result of SMART Analysis, the best outcome will be considerate as the best option to choose or the combination of options to choose then implemented in Kebab Mini Babe Juki’s business growth plan. Keyword: SMART Analysis, Side dish consumption, Business growth plan